2022
DOI: 10.1007/s10802-021-00887-w
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Trajectories in Adolescents and the Impact of Social Support and Peer Victimization

Abstract: This paper examines whether adolescents can be reliably categorized into subgroups based on their patterns of anxiety levels over time and whether low levels of social support from parents, peers, and their school, and high levels of peer victimization, predict a pattern of increasing anxiety. Participants were 3392 youth from the Longitudinal Study of Australia's Children (LSAC). Youth-reported anxiety was measured at three occasions at ages 12-13 years, 14-15 years, and 16-17 years, with social support and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Importantly, the current results are in line with findings in which stressful life events are commonly related to the development of anxiety and other internalizing disorders during adolescence ( Casline et al, 2021 , Green et al, 2010 ). Moreover, peer victimization (including overt and relational victimization) has been shown to predict increases in anxiety symptoms in adolescents ( Adrian et al, 2019 , Forbes et al, 2019 , Spence et al, 2022 , Stapinski et al, 2015 ). The current results also support recent findings in which relational victimization specifically has been shown to be related to increases in anxiety in adolescents ( Hamilton et al, 2016 ; Siegel et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the current results are in line with findings in which stressful life events are commonly related to the development of anxiety and other internalizing disorders during adolescence ( Casline et al, 2021 , Green et al, 2010 ). Moreover, peer victimization (including overt and relational victimization) has been shown to predict increases in anxiety symptoms in adolescents ( Adrian et al, 2019 , Forbes et al, 2019 , Spence et al, 2022 , Stapinski et al, 2015 ). The current results also support recent findings in which relational victimization specifically has been shown to be related to increases in anxiety in adolescents ( Hamilton et al, 2016 ; Siegel et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, stressful life events have been found to predict increases in anxiety and the development of internalizing disorders ( Casline et al, 2021 , Green et al, 2010 ). One specific type of interpersonal stressor, peer victimization, has been shown to predict increasing anxiety symptoms in adolescents ( Adrian et al, 2019 , Forbes et al, 2019 , Spence et al, 2022 , Stapinski et al, 2015 ). Peer victimization refers to experiencing repeated harmful and aversive aggression from peers, and includes overt victimization (e.g., physical aggression such as hitting or pushing) and relational victimization (e.g., the extent to which individuals experience peers purposefully attempting to harm their relationships with others through social exclusion or ridiculing; Storch et al, 2005a , Storch et al, 2005b ; Casper and Card, 2017 ).…”
mentioning
confidence: 99%
“…Differences between these sets of models were assessed via likelihood ratio tests. 26 , 27 Findings indicated that models fit significantly better when parameters were allowed to vary by sex ( p < .001), and thus LCGA models in the main analysis were subject to multiple-group analysis (MGA), which allowed class membership and model terms to vary by sex (4-class model: likelihood ratio test [LRT] χ 2 = 1196.8, df = 6, p < .001). 28 …”
Section: Methodsmentioning
confidence: 99%
“…To determine the number of trajectory classes that provided the optimal balance of fit and parsimony, model fit was iteratively assessed using multiple criteria, including entropy, the Bayesian information criterion (BIC), and log-likelihood comparing each model to a model with 1 fewer class. 24 , 27 , 29 As these statistics may prioritize fit improvement at the expense of parsimony, elbow plots of both BIC and log-likelihood values were visually examined. An elbow plot is a graphical tool used to assess the optimal number of latent classes.…”
Section: Methodsmentioning
confidence: 99%
“…Since Wave 5, LSAC has included 12 items from the original 18‐item validated Psychological Sense of School Membership (PSSM) scale which was developed and validated as a measure of adolescents' perceived belonging or psychological membership in the school environment (Goodenow, 1993). In accordance with previous population‐level studies of Australian adolescents which have demonstrated good reliability in the LSAC data set, the 12‐item PSSM scale is derived from responses ranging from 1 (Not at all true) to 5 (Completely true) to 12 positive and negative statements, such as “Most teachers at this school are interested in me” and “Sometimes I don't feel as if I belong here” with values ranging from 12 to 60 (negative items were reverse scored) (Mooney et al, 2022; Spence et al, 2022). Higher PSSM scores denote more positive youth perceptions of sense of school belonging (Goodenow, 1993).…”
Section: Methodsmentioning
confidence: 99%